Type 1 long QT syndrome and psychological stress in a laboratory setting. (August 2020) - Määttänen, Ilmari; Ravaja, Niklas; Henttonen, Pentti; Puttonen, Sampsa; Paavonen, Kristian; Swan, Heikki; Hintsa, Taina
Trait-like sensitivity to stress in long QT syndrome patients has been documented previously. In addition, mental stress has been associated with symptomatic status of long QT syndrome. We examined whether the symptomatic type 1 long QT syndrome patients would be more sensitive to mental stress compared to asymptomatic patients and whether there would be differences in task-related physiological stress reactions between type 1 long QT syndrome patients and healthy individuals. The study population consisted of 21 symptomatic and 23 asymptomatic molecularly defined KCNQ1 mutation carriers, their 32 non-carrier relatives and 46 non-related healthy controls, with mean ages of 37, 39, 35 and 23 years, respectively. Electrocardiography was utilised to calculate inter-beat interval and high frequency and low frequency heart rate variability. Blood pressure was measured and mean arterial pressure and pulse pressure were calculated. Stress was induced using three different tasks: mental arithmetic, reaction time and public speech. Stress responses of symptomatic and asymptomatic type 1 long QT syndrome patients were not statistically different in any of the stress tasks. Short-term physiological stress reactivity of symptomatic type 1 long QT syndrome patients appears to be normal and does not enhance the risk assessment of asymptomatic mutation carriers.